Love or Loath them, but we all need a board, don’t we? - Bray, Rachel; Esteveny, Laure (ICAReAlumni Conference Proceedings, 2019)
One of the top priorities of the newly designated Director General of CERN (the European Laboratory for Particle Physics) in 2016 was to establish a community, united by a shared pride in having contributed to CERN’s scientific endeavours, and provide an opportunity for alumni to maintain links with the Organization. It was to allow them to continue to share CERN’s values and support its activities, and serve as a valuable resource for members of personnel in the transition to work outside the laboratory. One of the top priorities of the newly designated Director General of CERN (the European Laboratory for Particle Physics) in 2016 was to establish a community, united by a shared pride in having contributed to CERN’s scientific endeavours, and provide an opportunity for alumni to maintain links with the Organization. It was to allow them to continue to share CERN’s values and support its activities, and serve as a valuable resource for members of personnel in the transition to work outside the laboratory. The CERN Alumni Network saw the light of day on 8 June 2017. Prior to its launch, an inter-departmental project group worked intensely over four months designing the CERN Alumni Network around its unique value proposition; establishing eligibility criteria, drawing-up offerings and carefully selecting a software provider for an alumni platform, amongst other things. The Office of Alumni Relations then had to articulate why CERN was launching such a network and reach out to potential members to encourage them to join. In parallel, we designed governance for the alumni programme along with terms of reference for a proposed CERN Alumni Board so that alumni would feel represented in terms of the direction in which the network would evolve.The reasons for establishing the CERN Advisory Board (CAAB) were:- To establish an embodiment of alumni expectations.- To provide a clear signal to alumni that the network would not only serve the purpose of CERN (and its scientific collaborations) but also their interests.- To enable a potentially huge external stakeholder of CERN to have a voice and a structure. - Strategic and of utmost importance in gaining input for the DG to define what is key for the community.- An element of the network‘s prestige.- Many of the professionals we had talked to (Oxford University/EMBL) had a board.The proposed presentation will briefly cover how we established an alumni network for an International Research Organisation, and in particular the role and implication of the CERN Alumni Advisory Board (CAAB) on the CERN Alumni Network. It will explore the mandate and purpose of the Board as specified, as well as describing the Board’s composition, how the board members are selected, by whom and on which criteria. Nearly two years down the line since the Network was created and with two CERN Alumni Advisory Board meetings under our belt, as well as many interactions outside the meeting, the proposed presentation will describe the recommendations taken on-board by the Director-General and subsequently highlight the impact and influence the Board has had on the Network. Furthermore, the presentation will identify the extent to which our expectations on the Board have been met so far. Finally, I will share with you, in light of our practical experience, our hopes for the CERN Alumni Board in the coming years.